Rating Estimation of the Company’s Competitiveness on the basis of a Normative Model (Journal of Economic Research & Business Administration, 2016)
The article presents a quantitative evaluation of competitiveness of oil and gas company in Kazakhstan. The company’s competitiveness has been estimated by a method of rating their financial and economic sta-tuses. This rating allows to monitor the status of the company in the dy-namics, to compare these dynamics and to determine its competitiveness. The financial and economic stability of the company is a precondition for economic activity. The paper calculates the estimation of competitiveness for oil company of Kazakhstan JSC «KazMunaiGas» Exploration Produc-tion.» Results of this research showed insufficient competitiveness of the company in question. The paper is structured as follows: The technique of rating estimation of the company’s competitiveness is presented, then The rating of competitiveness of the oil company under consideration is calcu-lated, and in the end the appropriate conclusions are made.
Keywords: competitiveness of the company; rating; financial and eco-nomic status of an oil and gas company; monitoring company’s financial status; analysis of company’s activity.